ANALISIS HUBUNGAN IMPLEMENTASI DISIPLIN DALAM UPAYA PENINGKATAN KINERJA GURU PADA STUDI KASUS PADA SMA NEGERI 01 KOTO KAMPAR HULU - Aqsa, Muhammad Ali (Eko dan Bisnis: Riau Economic and Business Review, 2021)
Abstract, This study aims to analyze the implementation of the relationship betweendiscipline and teacher performance in SMA Negeri 01 Koto Kampar Hulu. By using a totalsample of 32 people. In this research, the writer used quantitative research method usingSPSS data processing system. From the results obtained, the r count variable of workdiscipline is 0.641 and the value of r table is 0.338. so that r count> r table (0.641> 0.338)and a significant value of 0.000 <0.05, so it means that there is a positive and significantrelationship between the discipline variable and the performance variable. Finally, from thisstudy it can be concluded that there is a positive and significant relationship betweendiscipline and teacher performance at SMA Negeri 01 Koto Kampar Hulu.